Advance Purchase Agreement Sebagai Instrumen Pembatasan Memperoleh Vaksin COVID-19 dari Perspektif Hukum Internasional - Matakena, Mariah Agnes; Peilouw, Johanis Steny Franco (TATOHI: Jurnal Ilmu Hukum, 2021)
Introduction: During the COVID-19 pandemic, there was a global race to procure vaccines. Developed nations were able to procure prioritized access to many vaccines through Advance Purchase Agreements with vaccine developers due to their ability to invest more money, however this restricted developing nations to procure theirs.Purposes of the Research: This issue poses the question whether Advance Purchase Agreements as a form of restriction towards the procurement of COVID-19 vaccines is accepted from the perspective of international law. Methods of the Research: Type of research used is juridical normative, that is concept of law that is textual (law in books) or concept of law as a norm as guidance to how society behave in proper manner, by using case approach, statue approach and conceptual approach.Results of the Research: The results showed that Advance Purchase Agreement’s (APA) are not acceptable from the perspective of international law. The use of APA to secure prioritized access to vaccines at the expense of developing nations infringes on their right to health hence violates the principle of good faith due to being an instrument of restriction towards ability of developing nations to procure vaccines and their right to health. Furthermore, Advance Purchase Agreements, overstep the provisions of the Declaration on the TRIPS Agreement and Public Health 1995 as well as the Declaration of the Right to Development adopted by the General Assembly 1986.